Knowledge, Practices, and Environmental and Occupational Health Risks Associated with Electronic Waste Recycling in Cotonou, Benin - HOUESSIONON, Karel; Basu, Niladri; KEDOTE, N. Marius (My University, 2021)
Objective: The e-waste recycling is increasing worldwide, yet there remain outstanding environmental and occupational health concerns. Most research conducted on e-waste recycling has focused on only few countries (e.g., China, Ghana), thus there is a need to increase understanding of e-waste workers’ (recyclers’) knowledge and practices in other locations, that is purpose of this study. Methods: In a cross-sectional study conducted in Cotonou, Benin, 45 e-waste recyclers were interviewed from September to November 2018. Survey data was collected concerning their demographics, professional practices, and knowledge of occupational and environmental risks associated with e-waste recycling. Results: Most participants reported the following methods of material recovery of electronic items in declining orders: dismantling (97.8%) > sorting (91.1%) > incinerating (88.9%). Only 44.2% of the recyclers reported wearing ≥ 1 piece of personal protective equipment (PPE). More than 90% of e-waste workers noted that they disposed the e-waste in natural sites. About half, 46.7% believed that e-waste can pollute water and 71.1% considered that it can pollute air and soil. Recyclers reported several diseases including respiratory (67.4%), heart (62.8%), eye (65.1%), kidney (41.9%) and cancers (30.2%) could be linked to their work, respectively. Interestingly, we also found associations between the number of electronic items dismantled per month and self-report symptoms from the e-waste recyclers such as finding blood in urine and stool, wounds, dizziness, and itchy skin. Our results also indicated associations between the number of hours worked per day and blood in urine, dizziness, itchy skin and airway obstruction. Conclusion: To our knowledge this is the first study to interview e-waste workers in Benin. Doing this increase understanding of their work practices and knowledge to help inform intervention and prevention activities.
Keywords: E-Waste; Recycling; Occupational Health; Environment; Knowledge; Practice